A critique for eco‐evolutionary dynamics. (11th January 2019) - Hendry, Andrew P.
Abstract: A growing body of empirical work supports and informs the role of genetic variation and contemporary evolution in shaping ecological dynamics at the population, community and ecosystem levels. Although much progress has been made, I contend that reliance on several common empirical and inferential approaches is limiting forward progress in key areas, which leads me to several suggestions. More studies should focus on revealing eco‐evolutionary dynamics as they play out in the "real world, " as opposed to laboratories and mesocosms. At the community and ecosystem levels, increasing effort should be directed towards the importance of evolution acting through population density, as opposed to only direct per‐capita effects. More work should be directed towards the effects of whole‐community evolution, as opposed to the evolution of only particular focal species. New and innovative approaches are needed for studying how natural selection resists evolutionary and ecological change, thus generating cryptic eco‐evolutionary dynamics. Although simultaneous improvement on all of these fronts is perhaps impossible for any single research programme, even advances in one or more areas could dramatically improve our understanding of the prevalence, power and relevance of eco‐evolutionary dynamics. A plain language summary is available for this article. Abstract : Plain Language Summary